Hedging Strategies in Non-Science Theses: A Corpus-Based Analysis of Discussion Sections - Suratno, Antonius; Aydawati, Emilia Ninik (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
This study aimed to investigate the academic writings of students, which were stored in the students' theses repository. The primary goal was to explore how students employ politeness and caution strategy, often referred to as academic hedging when articulating their academic opinions in Chapter IV of the discussion section within their theses. Utilizing a corpus-based approach, the study analyzed 30 theses comprising over 100,000 words. The Antconc electronic analysis application was deployed to identify patterns of sentence expression and explore how students employed hedging techniques to present their academic ideas. The results indicate that student writers tended to rely heavily on the modal